Impurities in Drug Vials Intended for Intravitreal Medication. (2nd December 2020) - Pohl, Lisa; Strudel, Lisa; Dimopoulos, Spyridon; Ziemssen, Focke
Abstract : Sterility is an important prerequisite for minimizing the risk of severe vision loss due to endophthalmitis after intravitreal injections. We describe three cases series of incidents where an unclear contamination of the drug solution or syringe caused the injection process to stop and continue with a new preparation. During a period of 12 months with 30, 502 intravitreal injections at a tertiary center, wherein 7, 076 were of the drug Aflibercept drawn up from a glass vial, three cases of the critical incident reporting system relating to intravitreal injections were identified: (1) After a typical contact with the filter cannula, the glass of an Aflibercept vial was no longer intact. (2) In the course of another injection, there was a clear deposition of debris on the outer edge of the syringe when removing the attached filter cannula. (3) After inserting the syringe into the rubber top of the vial, a whitish particle of unclear origin was identified within the drug solution. Later, this contamination/particle was identified as part of the greyish rubber that was punched out with the cannula, according to the analyses of the material sent in and the manufacturer's investigations. Thus, even in busy clinics, visual inspection of the injection solution and materials used for impurities, preferably before and after pulling them out of a vial, must be an essential part of the injection process. Even when using ready-to-use prefilled syringes (PFS), vigilance must be kept high, knowing the risk of potential contamination.